Effect of Ethnomathematics in Teaching Functional Math Skills To Children With Intellectual Disability At Primary Level - N. Ilakkiya, V. Mrunalini (Journal of Neonatal Surgery, 2025)
Functional maths skills are important for everyone for an independent life. These skills are integrated with our cultural and traditional activities. This study aims to connect the ethnomathematics activities like Kolam and Pallanguzhi to practice functional math skills in children with mild to moderate intellectual disability. The Quasi-Experimental study design was used with an intervention group (n=19) and a control group (n=10), which included a pre-test and post-test. Madras Developmental Programming System and Functional Math Skills Assessment Tool, a teacher-made assessment tool, was used before and after the intervention. The study results were significant with p < 0.05. Intervention. Addition, subtraction, and multiplication showed a noticeable improvement. The limitations and future works are also discussed.